Review of Tobacco Industry Interference in Telangana State, India - Goel, Sonu; Bharatiya, Rajesh; Kumar, Rajeev; Kumar, Shravan; Yadav, Ravita; Vij, Jatina (Indian Journal of Community Health, 2025)
Background: Tobacco industry interference (TII) remains a significant barrier to effective tobacco control policies. Telangana, one of India’s major tobacco-producing states, is particularly vulnerable to industry influence. Despite the adoption of Article 5.3 of the WHO Framework Convention on Tobacco Control (FCTC), industry tactics continue to undermine public health efforts. Aims & Objectives: To document instances of TII in Telangana, analyze industry strategies, and provide evidence-based recommendations to mitigate their impact on tobacco control initiatives. Methodology: A descriptive study was conducted from 2019 to 2022, tracking TII incidents using a structured data collection tool. Information was gathered from newspapers, social media, government reports, and stakeholder interviews. Instances were categorized into six subtypes, including political influence, corporate social responsibility (CSR) activities, and manipulation of public opinion. Results: A total of 13 TII incidents were recorded, with the highest prevalence in 2020. CSR activities accounted for 92.3% of cases, primarily involving ITC Ltd. No official action was taken against these activities, highlighting gaps in enforcement. Conclusion: This study underscores the urgent need for stricter implementation of Article 5.3, increased monitoring of TII, and policy reforms to safeguard public health from industry influence.